2009
DOI: 10.2139/ssrn.1506905
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Repository Types: Challenges and Barriers for Subject-Based Repositories, Research Repositories, National Repository Systems and Institutional Repositories in Serving Scholarly Communication

Abstract: To cite this version:Chris Armbruster, Laurent Romary. Comparing Repository Types -Challenges and barriers for subject-based repositories, research repositories, national repository systems and institutional repositories in serving scholarly communication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 3 publications
0
38
0
2
Order By: Relevance
“…Findings in Bankier (2014) and Armbruster and Romary (2009) reports high usage of DSpace followed by Eprints which is next to DSpace in popularity although it is not as widely used as DSpace. Results from the survey conducted revealed that out of 2729 repositories worldwide, Dspace has the highest usage (42.3%) followed by EPrints (14.0%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings in Bankier (2014) and Armbruster and Romary (2009) reports high usage of DSpace followed by Eprints which is next to DSpace in popularity although it is not as widely used as DSpace. Results from the survey conducted revealed that out of 2729 repositories worldwide, Dspace has the highest usage (42.3%) followed by EPrints (14.0%).…”
Section: Resultsmentioning
confidence: 99%
“…The software are openly available and have a wider support from the global community of developers. Universities are free to compare different platforms depending on the features that best address their needs and that would make their repositories more successful (Armbruster and Romary, 2009). Generally, an institutional repository centralizes, preserves, and makes accessible the scholarly works generated by academic institutions, and form part of a larger global system of repositories which are indexed in a standardized way and searchable using a common interface (Sefton, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…9 http://oa.mpg.de/lang/en-uk/berlin-prozess/berliner-erklarung/ 10 usually referred to as institutional repositories (cf. Lynch 2003, and the wider distance analysis in Romary and Armbruster 2010) 11 in the form of deposit mandates (see Sale 2007) 12 see Armbruster and Romary (2010) for such a global comparison. which, across the years has become the reference environment for the French academic landscape.…”
Section: Defining Open Access Again?mentioning
confidence: 99%
“…When faced with the many alternatives currently available, it can be difficult for institutions to choose a suitable platform to meet their specific requirements. Several comparative studies between existing solutions were already carried out in order to evaluate different aspects of each implementation, confirming that this is an issue with increasing importance [16,3,6]. This evaluation considers aspects relevant to the authors' ongoing work, focused on finding solutions to research data management, and takes into consideration their past experience in this field [33].…”
Section: Introductionmentioning
confidence: 99%